Innovation through process oriented knowledgemanagement in a regional e-cluster system - Ute Hansen (European Regional Science Association (ERSA), 2005)
A regional e-cluster system and its cybernetics are characterised by a high degree of complexity which requires a comprehensive strategy. The identification of the key components of this e-cluster system and its interrelationships show that the component "knowledge management” is a critical and decisive process in an e-cluster system. ClusterNet builds the strategic frame for a process oriented knowledge management in a regional e-cluster system. The strategy of knowledge management consists of objectives, activities and measures to reach the vision that the resource of knowledge is used effectively in the cluster specific processes. Consequently this strategy requires the processes of knowledge management to be combined with the cluster processes in a technical and organisational way. The knowledge of an e-cluster can therefore just in time with the cluster processes be identified, acquired, developed, used, distributed and finally stored.
Keywords: 330